Plan de marketing estratégico para el mejoramiento de las ventas de la compañía BIO RENT s.a. en la ciudad de Guayaquil - Freire Guanoluisa, Angélica Desiree (2017)
The company BIO-RENT SA, which is part of the BIOGRUPO group of companies, is engaged in the commercialization of medical instruments and equipment of the brand ANDERSEN PRODUCTS and AVELLANUS, the latter being the least acquired due to the lack of knowledge on the part of the market, Which has caused that the sales only depend on the first and, therefore, there is no higher income. In the year 2015, the company invested only $ 96.80 in promotion and publicity, this being a consequence of the ignorance of the AVELLANUS brand by the market, since there has not been enough information on these products, which has been generating few sales. The general objective of the present work is to develop a strategic marketing plan that will help to achieve an improvement in the sales of the Company BIO-RENT S.A. In the city of Guayaquil……